Metabolic and cardiovascular features of the course of type 2 diabetes mellitus in men with hypogonadism - T. Yu. Demidova; D. V. Skuridina; A. M. Kasimova (Медицинский совет, 2022)
Introduction. Androgenic deficiency is an important pathogenetic element in the development of metabolic syndrome and cardiovascular diseases in men. It has been proven that in male patients with type 2 diabetes, hypogonadism develops much more often. Objective – to study the metabolic and cardiovascular features of the course of type 2 diabetes mellitus (T2DM) in men with androgen deficiency.Materials and methods. The study included 124 men with type 2 diabetes. To diagnose hypogonadism, the levels of total testosterone (T), sex hormone binding globulin (SHBG), albumin and luteinizing hormone (LH) were measured. Free testosterone (free T) levels were calculated using a calculator from Ghent University Hospital, Belgium. A retrospective analysis of case histories was carried out (spectrum of late complications, the presence of heart attacks and strokes, laboratory data – total cholesterol (CS), triglycerides (TG), fasting blood plasma glucose, basal insulin level, glycated hemoglobin (HbA1c)). The HOMA-IR index was used to determine the degree of insulin resistance.Results. The average age of men was 57.39 ± 9.41 years. The incidence of laboratory-confirmed hypogonadism is 50.81%. An average positive correlation was found between androgen deficiency and the incidence of non-fatal cardiovascular events (r = 0.45, p < 0.05). There was no statistically significant relationship between the presence of hypogonadism and the incidence and degree of late complications of T2DM. Patients with low T levels tended to have higher HOMA-IR values compared to patients with normal T levels (p < 0.05). At the same time, the indicators of carbohydrate and lipid metabolism did not differ significantly in these groups (p > 0.05).Conclusions. The revealed incidence of hypogonadism in men with T2DM corresponds to the data of international studies. The presence of a significant correlation between low testosterone levels and cardiovascular events in patients with T2DM suggests that hypogonadism can be used as an additional criterion for cardiovascular risk. Testosterone deficiency exacerbates insulin resistance, which can lead to weight gain and impair carbohydrate metabolism.